1999
DOI: 10.1300/j069v18n02_03
|View full text |Cite
|
Sign up to set email alerts
|

Physician Substance Use by Medical Specialty

Abstract: Self-reported past year use of alcohol, tobacco, marijuana, cocaine, and two controlled prescription substances (opiates, benzodiazepines); and self-reported lifetime substance abuse or dependence was estimated and compared for 12 specialties among 5,426 physicians participating in an anonymous mailed survey. Logistic regression models controlled for demographic and other characteristics that might explain observed specialty differences. Emergency medicine physicians used more illicit drugs. Psychiatrists used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
54
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(71 citation statements)
references
References 32 publications
7
54
0
5
Order By: Relevance
“…Our findings are in agreement with earlier mainly cross-sectional studies focused on specialized physicians, as they show higher rates of self-reported burnout, mental disorders, and smoking among psychiatrists when compared to other physicians (3)(4)(5)(6)(7)(8)(9)(10), and studies showing more favorable health behaviors among surgeons and pediatricians (7)(8)(9)(10)(11)(12). We found that the differences between specialties in our study with the majority of participants being nurses were quite similar to those reported for physicians.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in agreement with earlier mainly cross-sectional studies focused on specialized physicians, as they show higher rates of self-reported burnout, mental disorders, and smoking among psychiatrists when compared to other physicians (3)(4)(5)(6)(7)(8)(9)(10), and studies showing more favorable health behaviors among surgeons and pediatricians (7)(8)(9)(10)(11)(12). We found that the differences between specialties in our study with the majority of participants being nurses were quite similar to those reported for physicians.…”
Section: Discussionsupporting
confidence: 92%
“…In hospital settings, there is some evidence to suggest differences in health and health behaviors between staff working in different specialties (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Studies of physicians show elevated rates of "burnout", mental disorders, substance use, and suicide among psychiatrists, anesthesiologists, and physicians working in emergency or primary care although the association is not robust (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In contrast, surgeons and pediatricians have reported lower rates of substance use (7), although this is not a universal finding (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…18 Studies pre-dating the 1980s identified meperidine, a synthetic opioid, to be the most frequently abused controlled substance, followed closely by benzodiazepines and barbiturates. 19 In line with our results, fentanyl has since superseded meperidine as the opioid most often implicated in reported cases of chemical dependence. 3,10,20 There were two cases of propofol abuse reported in our results.…”
Section: Discussionsupporting
confidence: 89%
“…[5][6][7] This postulate is supported by data on major opioid use by anesthesiologists (morphine, meperidine, fentanyl, and other injectable narcotics) and minor opioid use by family physicians (hydrocodone, oxycodone, codeine, and other oral drugs). [5][6][7] In contrast with physicians in other specialties who primarily administer medications by proxy and therefore do not touch drugs or have them in their possession, anesthesiologists directly administer fentanyl, sufentanil, alfentanil, and remifentanil on a daily basis; although protocols to prevent diversion are typically in place at every hospital and outpatient surgical center, they are not fail-safe. 8 If use of major opioids results in a more aggressive manifestation and progression of addiction, that would partly account for the overrepresentation of anesthesiologists in physician treatment and monitoring programs.…”
mentioning
confidence: 93%